Metafora Konseptual Bertema Rihlah (Jalan-Jalan) pada Majalah Gontor: Analisis Semantik Kognitif - Trian Ramadhan Nuryadin; Tajudin Nur (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This research is a cognitive semantic analysis and uses descriptive qualitative methods. The problems discussed in this study are the types of conceptual metaphors, namely (1) structural metaphors, (2) orientational metaphors, (3) metaphors. The theory used is the conceptual metaphor from Lakoff & Johnson (2003) as the main theory and the image scheme from Cruse & Croft (2004) theory. The data is taken from the Gontor magazine with the theme of "rihlah" (traveling). Based on the analysis conducted, 11 conceptual metaphor data were found, with the following details: seven structural metaphors are the concepts of the meaning of decoration, protection, limb, the taste of food, expenditure, nature, and fame; one orientational metaphor with the concept of the meaning of quality; and three ontological metaphors with the concept of well-known meaning, heredity, and quality of goods. The image schemes found were one power/control scheme, two existence/process schemes, two identity/conformity schemes, and six existence/object schemes.